Indigenous traditional knowledge (ITK) from forest dwellers of Gondia district, Maharashtra - Kamble, Rahul B; Mungole, Arvind; Maske, Mahesh; Chaturvedi, Alka; Chaturvedi, Arun (Journal of Ecobiotechnology, 2011)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Indians have great knowledge of phytomedicines. This valuable knowledge has been conserved in the living folk traditions in ethnic communities.Ã‚Â  An attempt has been made to explore traditional medicinal knowledge of plant materials, available in forest villages of Goregaon and Deori forest range of Gondia district, Maharashtra state. Gondia is one of the prominently categorized districts with maximum tribal population in Maharashtra which includes mostly Gond, Gowari, Halbi, Manah tribes with great numbers. In this study we documented about 49 plant species of various families which are commonly used by the tribal people to cure some common diseases viz. Dysentery, acute headache, toothache and carries, urinary troubles, skin diseases, antidote against snake bite, vomiting and many more. Ethnobotanical information were gathered through several visits, group discussions and cross checked with traditional medical practitioner of the study area.